(untitled) (Archaeologia Adriatica, 2023)
In this paper (based on processed cranium fragments) the authors posit that the remains in question may be those of Archbishop Petar Bogdani. Special attention is paid to the general overview of the political situation in the territory of what is present-day Kosovo in the late Middle Ages, where (due to riots and political transition during the Ottoman occupation) persons appeared on the political scene who influenced the formation of a modern ideology. This undoubtedly influenced the consciousness of the population and left traces that, depending on the geopoltical context, do not differ all that greatly from the situation in 20th century Kosovo. The story of Pjetër Bogdani and the mystery of his tomb, presented briefly in this article, should be considered as catalyst for arousing academic research inside and outside of the country—especially for archivists